2020
DOI: 10.1186/s12893-019-0658-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification for early bacteremia after living donor liver transplantation: a retrospective observational cohort study

Abstract: Background: This study investigated perioperative clinical risk factors for early post-transplant bacteremia in patients undergoing living donor liver transplantation (LDLT). Additionally, postoperative outcomes were compared between patients with and without early post-transplant bacteremia. Methods: Clinical data of 610 adult patients who underwent elective LDLT between January 2009 and December 2018 at Seoul St. Mary's Hospital were retrospectively collected. The exclusion criteria included overt signs of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…In some studies, infection was confirmed as the main cause for both short-and long-term death (20). Park et al (21) reported that 57 (9.7%) recipients who underwent living donor LT experienced infection within 1 month after surgery and 34 recipients lost their lives due to infection, and the incidence of infectious death was 5.7% (34/596). A study designed by Kwak et al (17) demonstrated that pneumonia, which occurred in 46.3% of patients, was the most common cause of all infectious deaths.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, infection was confirmed as the main cause for both short-and long-term death (20). Park et al (21) reported that 57 (9.7%) recipients who underwent living donor LT experienced infection within 1 month after surgery and 34 recipients lost their lives due to infection, and the incidence of infectious death was 5.7% (34/596). A study designed by Kwak et al (17) demonstrated that pneumonia, which occurred in 46.3% of patients, was the most common cause of all infectious deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Based on changes in the CBC after disease onset, the NLR has a good ability to differentiate patients who will become critical within 4 weeks after disease onset. The NLR is the ratio of neutrophils to lymphocytes in peripheral blood, and its clinical value in infectious diseases or inflammation has been gradually appreciated 22,23,24 . In the early stage of this epidemic, a study carried out by Beijing Ditan Hospital Affiliated to Capital Medical University 25 showed that if a patient had an NLR > 3.13 and was over 50 years old, he/she was more likely to develop severe disease, and intensive care should be considered as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…The NLR is the ratio of neutrophils to lymphocytes in peripheral blood, and its clinical value in infectious diseases or inflammation has been gradually appreciated. 22,23,24 In the early stage of this epidemic, a study carried out by Beijing Ditan Hospital Affiliated to Capital Medical University 25 showed that if a patient had an NLR > 3.13 and was over 50 years old, he/she was more likely to develop severe disease, and intensive care should be considered as early as possible. This study also found that the NLR had a better differentiation value than other parameters for identi- invaded by the pathogen.…”
Section: Ta B L E 1 Epidemiological and Clinical Characteristics Of Pmentioning
confidence: 99%
“…Donor-graft findings included age, sex, BMI, graft-to-recipient weight ratio, total ischemic time, fatty change, and hepatic vascular circulation. Postoperatively, we measured glucose levels from the first postoperative day for 1−4 weeks after surgery; early bacteremia status (during the first 4 weeks after surgery) [ 22 ]; and new-onset DM developing during the follow-up period [ 23 ].…”
Section: Methodsmentioning
confidence: 99%